PEMILIHAN JENIS WRAPPING SYSTEM DAN OPTIMASI DIMENSI TALI BAJA TRAKSI SUSPENSI PADA ELEVATOR PENUMPANG: Studi Kasus Gedung Bank X - Eriel Yusran Abdikar (2024)
The diameter of the steel rope is the starting of the design of all lifting systems that use steel ropes as a lifting component. In this case, the larger the diameter of the steel rope, the larger the pulley diameter, which has implications for construction and operating costs. On the other hand, the smaller the diameter of the rope, the smaller the diameter of the sheave or pulley, which causes an increase in the amount of steel rope required. This dilemma can only be resolved by involving other factors that influence operational safety and fatigue of steel rope materials, namely safety factors, life cycle, number of steel ropes and elongation, which respectively are the priority levels for selecting the optimum steel rope diameter. The aim of this research is Determine the type of wrapping system that is capable of lifting loads on the side of the train without slipping and determine the type of steel rope construction and optimize the diameter of the main and alternative suspension traction steel ropes. This research method uses two approaches, namely the academic approach and the engineering approach referring to user needs in the form of passenger capacity, transport speed and working height which are then technically translated by determining the carrying capacity, transport speed, pit height, working height and overhead. Based on the calculation results, the choice of wrapping system specifications uses a winding angle of 175 degree with Wrapping type Single Wrape Traction Machine Above with U105 degree or to guarantee a high level of security, a winding angle of 340 degree is chosen with Wrapping type Double Wrape Traction Machine Above with U round and for lifting speed The elevator according to specifications is met by the construction of steel ropes 8x19S-CGFS DUAL TENSILE 1570/1770 MPa-1620/1770 MPa, namely steel ropes with a diameter of 12 mm and 12.7 and the one that best meets the requirements is the one with a diameter of 12 mm, which is the smallest diameter. Keywords: Steel rope, diameter, wrapping, traction, Elevator.